THE IMPORTANCE OF THE EUROPE-ASIA TRANSPORT CORRIDOR: ANALYSIS OF TRANSPORT ROUTES BETWEEN CHINA AND EUROPE - Chazzaoui, Tamima Armando Mamede (Revista Sistemática, 2021)
This article explores the growing importance of the Europe-Asia transport corridor, with a particular focus on the logistics routes connecting China and Europe. It examines how rail, maritime, and road networks contribute to the efficiency, sustainability, and resilience of transcontinental trade flows. The paper highlights the strategic role of China’s Belt and Road Initiative and the European Union’s Global Gateway in shaping infrastructure development, regulatory cooperation, and geopolitical influence. Drawing on recent data and academic research, the study analyzes the strengths and limitations of different transport modes, including the China-Europe Railway Express and maritime shipping via the Suez Canal. In addition, the article addresses environmental concerns, emphasizing the carbon reduction potential of shifting freight from road and sea to rail. Technological innovations such as digital platforms, automated freight terminals, and smart customs systems are also considered key enablers of improved logistics performance. The analysis shows that a coordinated and multimodal approach is essential for optimizing the corridor’s strategic value. Ultimately, the findings emphasize the need for continued investment in infrastructure, policy harmonization, and sustainability practices to ensure the long-term viability and competitiveness of the corridor in a rapidly evolving global trade environment.